Biochemical Properties of Vertisols and Performance of Fenugreek (Trigonella foenum-graecum L.) with Treated Industrial Effluent Irrigation - and Dipika G. Rangani, Sanjay Arora (Journal of the Indian Society of Soil Science, 2016)
Use of treated industrial effluent for irrigating agricultural crops has great significance to crop yield, soil fertility and soil biological activity. A field experiment was conducted on a Vertisol with fenugreek as test crop to compare treated industrial effluent from NCPL, Bharuch, Gujarat with best available tubewell water (BAW) as irrigation water. Plant height increased by 22.9 per cent with treated effluent irrigation as compared to only BAW. Highest fenugreek seed and straw yields were 42.8 and 74.0 g m-2, respectively in 50% diluted effluent with BAW, and differed significantly from other options. Total N, P and K uptake by the plant parts was also improved when irrigated with treated effluent. The soil properties after harvest were influenced when treated effluent with or without dilution was used for irrigation. Soil organic carbon content increased due to irrigation with treated effluent as compared to BAW alone. Similarly, build-up of native N and P was observed in plots receiving treated effluent for irrigating the crop.